Ecological and phytocenotic peculiarities of anthropogenic changes of the stow “Holendernya” - Блінкова, О. І.; Лавров, В. В.; Сагдєєва, Т. Ю.; Житовоз, А. В.; Березніченко, Ю. Г. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The factors and ecological and phytocenotic peculiarities of anthropogenic digression of forest plantations of the stow «Holendernya» of the State Dendrological Park «Alexandriya» have been characterized. Changes of ecological conditions of the stow were caused by unregulated recreation, physical and biological contamination, reconstruction of the forest type in the landscape park type and mechanical action (collection of herbs, mushrooms). The spatial distribution of changes of ecological conditions of edaphotop and aerotop in a forest ecosystem has been determined by means of factor analysis. The relevant changes in the structure of vegetation, depending on the distance to the city Bila Tserkva and river Ros have been also analyzed. Oak plantation of the stow degraded at the ІІІ stage of recreational digression. Anthropogenic changes of the stow have been shown by biomorphological spectrum, types of ecological strategies, ecomorphical structure of herbaceous cover. The greatest development of perennials has been observed in the core of plantations, the least – in the suburban park area. Non-rosellate herbal plants and plants that do not have special modifications of underground shoots dominated in all zones of the stow. Stress-tolerators and competitors were absent, species of mixed type of ecological strategy prevailed in conditions of significant human transformation in grass cover. Hydromesophytes and mesophytes dominated among hidromorphes. Nitrification of ecotypes has been revealed by the distribution of nitromorphes. Development of adventives species has been revealed in all zones of the stow. We proved that the plant cover, especially herbaceous, is sensitive to the change of ecological regimes within forest environment and could be an integrated indicator of such changes.